2020
DOI: 10.3390/brainsci10090625
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Agenesis: An Insight into the Etiology and Spectrum of Symptoms

Abstract: Brain hemispheres are connected by commissural structures, which consist of white matter fiber tracts that spread excitatory stimuli to various regions of the cortex. This allows an interaction between the two cerebral halves. The largest commissure is the corpus callosum (CC) which is located inferior to the longitudinal fissure, serving as its lower border. Sometimes this structure is not completely developed, which results in the condition known as agenesis of the corpus callosum (ACC). The aim of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 64 publications
(105 reference statements)
1
42
0
Order By: Relevance
“…Surprisingly, our patients showed remarkable muscle strength and often hypertonia; hypertonic limbs with brisk reflexes were also previously reported for one case (Skraban et al, 2017). We can speculate that this ambiguous muscle tone phenotype, as well as the diverse type of walking, could be related to the brain MRI findings, predominantly affecting the white matter such as corpus callosum anomalies (Edwards et al, 2014; Hofman et al, 2020), enlarged ventricles, white matter volume loss, and mild cerebellar hypoplasia (Skraban et al, 2017). Furthermore, the combination of wide‐based gait and spastic and/or stiff‐leg gait are often reported.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, our patients showed remarkable muscle strength and often hypertonia; hypertonic limbs with brisk reflexes were also previously reported for one case (Skraban et al, 2017). We can speculate that this ambiguous muscle tone phenotype, as well as the diverse type of walking, could be related to the brain MRI findings, predominantly affecting the white matter such as corpus callosum anomalies (Edwards et al, 2014; Hofman et al, 2020), enlarged ventricles, white matter volume loss, and mild cerebellar hypoplasia (Skraban et al, 2017). Furthermore, the combination of wide‐based gait and spastic and/or stiff‐leg gait are often reported.…”
Section: Discussionmentioning
confidence: 99%
“…17,38,39 Partial or full agenesis of the corpus callosum (ACC [MIM: 217990]) was also present in five of the individuals and is a common malformation with diverse etiology, including variants in >20 genes. 40 In these genetic disorders, ACC is often variable and its expression may differ between mice and humans. For instance, in ACCPN (peripheral neuropathy with agenesis of the corpus callosum, or Anderman syndrome [MIM: 218000]), which is caused by loss-of-function variants in SLC12A6 encoding the K þ -Cl À -cotransporter KCC3, 41 penetrance is incomplete in humans and preliminary studies in Kcc3 À/À mice indicated that they have a normal corpus callosum.…”
Section: Loss Of Clc-3 Causes Severe Neurological Disease In Both Mic...mentioning
confidence: 99%
“…Anomalies of the corpus callosum (CC) are among the most common central nervous system (CNS) malformations diagnosed during the fetal period [1][2][3][4][5] . These anomalies present commonly in association with other CNS and extra-CNS anomalies, aneuploidies or genetic syndromes and carry a high risk of adverse neurodevelopmental outcome [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%